Politik Hukum Pemakzulan Presiden Di Indonesia - Irham, Muhammad; Soplanit, Miracle (Faculty of Law, Universitas Pattimura, 2022)
The term of office of the President in a presidential system is a fixed term of five years and cannot be dropped during his term of office. The legal politics of the presidential impeachment process prior to the amendment of the 1945 Constitution did not have a clear mechanism to impeach the president. The impeachment of the president is determined by the procedures and political power in the People's Consultative Assembly (MPR). This is a problem in the presidential system, because there is no legal process for impeaching the president. After the amendment to the 1945 Constitution, the concept of impeachment of the president was based on the idea of a presidential system, where the president cannot be dismissed only through a political process, but there must be a legal process first. Therefore, this article will explain how the dynamics of legal politics in the process of regulating the impeachment of the president in Indonesia in the 1945 Constitution. The research method used is normative juridical. From the analysis that the author did, it was found that the political aspirations of the impeachment arrangement of the president want the dismissal of the president no longer based on political interests, but must go through legal reasons and through the legal process, as a form of embodiment of Indonesia as a legal state with a presidential government system.